INTRODUCTION TO KALIMANTAN CULTURE USING AUGMENTED REALITY TECHNOLOGY - Oktavia, Chaulina Alfianti; Riyadi, Achmad Buyung (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Central Kalimantan is a province consisting of 13 regencies and 1 city with the capital city of Palangkaraya. Many people, especially the younger generation, do not know the various cultures of Central Kalimantan such as traditional houses, clothes, traditional weapons, and so on. To facilitate the introduction of this culture an application is designed using Android-based Augmented Reality technology. Augmented Reality was designed using marker technology. From the test results, markers can be detected properly and can recognize and display Central Kalimantan cultural objects such as traditional houses, clothing, traditional weapons, and others. With the Augmented Reality application, it can make it easy for users to recognize the culture of Central Kalimantan. Based on the test results which included testing the AR Central Kalimantan application, the content of the AR Central Kalimantan application, and the display aspect obtained a score of 86%, it can be concluded that the application has been running well.